METODE SEJARAH LISAN DAN HISTORIOGRAFI PERIODE JEPANG DI PULAU DI MOROTAI - Abbas, Irwan (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
Efforts to reconstruct the local history during the Japanese occupation, the era of World War 2 in Morotai be an interesting thing to be studied and researched. The existence of Morotai in the lips of the Pacific Ocean has strategic value for both sides, both Allied soldiers led by the United States and the Japanese army to serve as centers of the military. Various historical artifacts spread over land and sea to witness the heroic history of the events that have occurred on Earth Morotai. Reconstruct the history of Japanese period is not easy, as there was no written document in the form of archives as a primary source in historiography. Oral history method (oral history) is an alternative in the review for the period. Oral history is one of the historical sources, which can be used as the writing of history. Through in-depth interviews with actors history obtained the historical fact that can be a source of important information about the events that occurred. Sadly, many actors and witnesses of history who have died so that informants who are still alive are very limited in number, plus the age constraints of the elderly so it is not easy to get the desired information and various other obstacles complicate efforts to reconstruct the history at that time. Need the support of all elements of society to facilitate trace the history of World War 2 on the island of Morotai.